Studi Kecepatan Spindel Mesin Bubut Terhadap Nilai Unit Horse Power (UHP) Pada Proses Pembubutan Baja Karbon Rendah - Saputra, Fahri Ari; Samhuddin, Samhuddin; Aminur, Aminur (Teknik Mesin Universitas Halu Oleo, 2021)
The machining process is a manufacturing process where the main process is removing or removing some of the material from a basic material which can be in the form of a shaft so that it meets the desired shape and quality. The purpose of this study was to determine the effect of the rotational speed of the lathe spindle on the value of Unit Horse Power (UHP) in the low carbon steel turning process. The study used carbon steel material in the form of a cylinder with an initial diameter of 40 mm and a length of 150 mm. The cylindrical workpiece is turned with a depth of 1 mm at various speeds, namely 95 rpm, 130 rpm and 180 rpm. The results showed that the rotational speed of the lathe spindle affects the value of the unit horse power (UHP). The higher the spindle rotation of the lathe, the greater the UHP obtained, where the highest UHP occurs at 180 rpm with a UHP value of 0.00030 and the lowest UHP. found in round 130 with a UHP value of 0.00016. High rotation causes a large force so that the vibration of the lathe tool is even greater.Keywords: Lathe process, carbon steel, spindle rotation.